Being autistic during the COVID-19 process: from a public health nurse’s perspective - Yildirim, Nilufer; Elmas, Semra (International Journal Of Community Medicine And Public Health, 2022)
Parents have an important role in supporting, controlling and managing autistic children's daily life at home. During the COVID-19 pandemic, routine life has changed and a decision for social isolation has been made. The purpose of this case study is to provide an overview of how the child with autism performs daily activities during the pandemic process, the state of self-care skills, and what are the daily developer activities at home. Data collection methods used in this study are interviews and observations. The results of this study show that children with autism can be supported, supervised and guided effectively by their parents at home. It is thought that the case report will provide an idea for diagnosis, and create a training and consultancy program for public health nurses working with autistic children in the field.